Tradable parking permits as a transportation demand management strategy: A behavioural investigation. (January 2022) - Bao, Helen X.H.; Ng, Joelle
Abstract: Tradable parking permit schemes can be an effective transportation demand management strategy for cities where cars are viewed as a status symbol and wide adoption of shared transportation modes face resistance. We investigate the feasibility and effectiveness of tradable parking permit schemes in high density cities with parking constraints. We focus on the effect of four behavioural factors, namely, reference dependence, endowment effect, social nudge, and environmental consciousness. Online experiments are conducted via Amazon Turk Prime platform, with participants recruited from large cities in China. Our investigation on reference dependence and endowment effect suggest that tradable parking permit schemes is feasible and efficient. Environmental consciousness can improve the schemes' effectiveness in encouraging participants to switch to public transport, but social nudge shows no significant effect. Our study provides much-needed empirical findings about tradable credits for transportation management on the individual level. Highlights: Empirical findings about tradable credits for transportation management on the individual level Online experiments using data from 101 large cities in 26 provinces in China Reference dependence, endowment effect, social nudges, and environmental consciousness Tradable parking permit schemes is feasible and efficient in cities with parking constraints.